Theological Pedagogies: Reflections on Person, Place, Process and Practices in Teaching and Learning Theology in Times of Crisis - Shantelle Weber; Bård Norheim; Ian Nell; Katleho Mokoena; Josleen Rutere; Anita Cloete; Gunnar Innerdal; Nick Shepherd; Reginald Wilfred Nel; Vigdis Berland Øystese; Rune Øystese; Christo Thesnaar; et al. (AOSIS, 2025)
In times of crisis, the role of theology in education becomes increasingly vital. The ability to navigate these challenging times requires innovative and effective teaching practices that are grounded in both traditional and contemporary pedagogical insights. This scholarly book seeks to explore changing theological pedagogies in teaching theology, with a particular focus on the person, place, process and practices involved in teaching and learning theology during times of crisis. The following themes are explored: Person: How does the identity and background of the teacher and learner influence the teaching and learning of theology in times of crisis? Place: How does the physical, cultural and social context of teaching theology impact pedagogical approaches during crises? Process: What teaching methods and strategies are most effective in facilitating theological learning and reflection during times of crisis? Practices: What are the best practices for integrating theory and practice in teaching theology, especially in times of crisis?